2006
DOI: 10.1074/jbc.m511059200
|View full text |Cite
|
Sign up to set email alerts
|

G1/S Arrest Induced by Histone Deacetylase Inhibitor Sodium Butyrate in E1A + Ras-transformed Cells Is Mediated through Down-regulation of E2F Activity and Stabilization of β-Catenin

Abstract: Tumor cells are often characterized by a high and growth factor-independent proliferation rate. We have previously shown that REF cells transformed with oncogenes E1A and c-Ha-Ras do not undergo G 1 /S arrest of the cell cycle after treatment with genotoxic factors. In this work, we used sodium butyrate, a histone deacetylase inhibitor, to show that E1A ؉ Ras transformants were able to stop proliferation and undergo G 1 /S arrest. Apart from inducing G 1 /S arrest, sodium butyrate was shown to change expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 49 publications
6
46
0
Order By: Relevance
“…6F and 7B). Thus, in line with our data that NaB inhibits clonability of mERas cells in a soft-agar assay and formation of clones on a plastic surface, 5 here we show that NaB effectively inhibits migration and invasion through a porous of membrane, while rapamycin cancels those NaB effects that are connected with migration. Importantly, these effects of rapamycin are p21 Waf1 -dependent.…”
Section: Waf1supporting
confidence: 77%
See 3 more Smart Citations
“…6F and 7B). Thus, in line with our data that NaB inhibits clonability of mERas cells in a soft-agar assay and formation of clones on a plastic surface, 5 here we show that NaB effectively inhibits migration and invasion through a porous of membrane, while rapamycin cancels those NaB effects that are connected with migration. Importantly, these effects of rapamycin are p21 Waf1 -dependent.…”
Section: Waf1supporting
confidence: 77%
“…17 Taken together, these data serve as evidence that accumulation of senescence-associated γH2AX foci can be a trigger of hyperactivation of pathways involved in cell senescence, as was recently proposed on a mouse model, 18 or its consequence. 9,19 Thus, although HDACI exert antiproliferative effect due in part to activation of the p21 Waf1 gene transcription, 5 nevertheless, p21…”
Section: Waf1mentioning
confidence: 99%
See 2 more Smart Citations
“…We also performed cell cycle analysis in the AQP1-overexpressing cells after incubation with the synchronization drug, sodium butyrate, which synchronizes cells in G1 by inhibiting cyclin E activity. 92 The cell cycle profile in the presence of butyrate showed that cells that overexpressed AQP1 are more resistant to being synchronized by this drug. The higher expression in these cells of cyclin E1, which regulates the checkpoint for G1-S transition, [89][90][91] could support this response to butyrate treatment.…”
Section: Cell Cycle and Aqpsmentioning
confidence: 99%